The application of microalgae feeding regime on whiteleg shrimp culture in each stage : a mini review - Arsad, Sulastri; Siallagan, Rubina Melini; Lusiana, Evellin Dewi; Musa, Muhammad; Mahmudi, Mohammad; Sari, Luthfiana Aprilianita; Prasetiya, Fiddy Semba; Nadirah Musa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Feed management in shrimp culture aims to improve the quality of shrimp organisms. The application of the feeding regime in shrimp culture has been developed to determine the best formulation of diet in order to maximize growth rate and survival rate of shrimp by increasing feed efficiency and minimizing waste. The application of the feeding regime is closely related to the understanding of the physiological and morphological aspects of shrimp from the larval stage to the adult stage. The success of the application of feed management with the application of the feeding regime will be a solution to the problem of the high costs of feed needed in shrimp culture. The best formulation of diet in shrimp culture in the N6-P3 stage is microalgae, at the M1-PL10 stage is zooplankton, and in the juvenileadult shrimp stage is artificial feed. Microalgae can significantly increase the survival rate and growth rate of shrimp at the hatchery stage. This article aimed to examine the effect of the application of feeding regime using different diet formulations to produce the highest growth performance of shrimp in shrimp culture based on the morphological and physiological aspects of shrimp.